Política de integração, infraestrutura e territorialidades: análise dos projetos de desenvolvimento na Pan-Amazônia e os impactos para as populações indígenas dos rios Tapajós (BR) e Putumayo (CO) - BIERI, Márcia Eloisa Lasmar (Universidade Federal do Pará, 2021)
This study contributes to the debate on the public policies implementation of development based on the Brazilian and Colombian government actions, in a scenario where the consequences of these actions affect the destiny of indigenous people, and the regional development ideology proposed by the State favors only the national and international economic and political interests. A development policy that is adverse to indigenous people, who do not have the opportunity to participate in the discussions to face government proposals, even though their rights are guaranteed by the legislation in force both in Brazil and Colombia. Within the scope of these development policies, emerge the state apparatus and the power exercise for the construction of megaprojects that move a large amount of capital and affect populations in an irreversibly way, which, as well as will be seen, occurred and occurs with the Munduruku and Sionas people, forced to the remotion of their traditional territories, leaving behind their historical sources, their sacred and surviving places.